2014
DOI: 10.1002/rcm.7024
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral characterisation of a polar, esterified fraction of an organic extract of an oil sands process water

Abstract: The results suggest the more polar acidic organic SO3 constituents of OSPW include C15-28  S-containing, alicyclic and aromatic hydroxy carboxylic acids. SO5 species are possibly sulphone analogues of these. The origin of such compounds is probably via further biotransformation (hydroxylation) of the related S-containing carboxylic acids identified previously in a less polar OSPW fraction. The environmental risks, corrosivity and oil flow assurance effects should be easier to assess, given that partial structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…To date, knowledge of the chemical identity of sulfur‐ and nitrogen‐containing species in OSPW is very limited . Only recently have a few S‐containing acids been characterized, but to our knowledge the identification or characterization of N‐containing species in OSPW has not yet been investigated. In the same analytical run, the above optimized SFC method for NA isomers also showed excellent separation capability for isomers among the major classes of N‐ and S‐containing compounds in OSPW.…”
Section: Resultsmentioning
confidence: 99%
“…To date, knowledge of the chemical identity of sulfur‐ and nitrogen‐containing species in OSPW is very limited . Only recently have a few S‐containing acids been characterized, but to our knowledge the identification or characterization of N‐containing species in OSPW has not yet been investigated. In the same analytical run, the above optimized SFC method for NA isomers also showed excellent separation capability for isomers among the major classes of N‐ and S‐containing compounds in OSPW.…”
Section: Resultsmentioning
confidence: 99%
“…However, Orbitrap mass analyzers have a ∼10-fold lower mass resolution that limits separation of peaks in the higher mass range ( Supplementary Table S1). Even so, Orbitrap instruments have been successfully applied for characterizing complex natural organic materials ( Supplementary Table S2), including DOM (Pomerantz et al, 2011;Cortés-Francisco and Caixach, 2015;Hawkes et al, 2016), humic and fulvic acids (Galindo and Del Nero, 2015;Nebbioso and Piccolo, 2015), petroleum and bio-oilrelated material (Pomerantz et al, 2011;Zhurov et al, 2013;Rowland et al, 2014;Staš et al, 2015), and extraterrestrial organic materials (Danger et al, 2013;Smith et al, 2014), yet it remains unclear how comparable the results of both instrument types are. Addressing this question is even more pivotal when aiming to compare trends in larger-scale DOM sample sets achieved on different instruments (Swenson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Undiluted OSPW have been shown to be toxic to numerous organisms at the concentrations found in tailings ponds and since this toxicity has been largely attributed to the NA content (He et al, 2012;Marentette et al, 2015), considerable effort has been made to develop methods for monitoring the extremely complex distributions of NA found in OSPW . High and ultra-high resolution mass spectrometry methods have revealed that OSPW contain an extensive range of NA (Yi et al, 2015), beyond so-called 'naphthenic' or cyclic non-aromatic species (Rowland et al, 2014;Barrow et al, 2015). Many analytical methods also include a chromatographic separation step (e.g.…”
Section: Introductionmentioning
confidence: 99%